Parental perspectives on negotiations over diet and physical activity: how do we involve parents in adolescent health interventions?. Issue 9 (24th June 2021) - Shaw, Sarah; Correia Simao, Sara; Jenner, Sarah; Lawrence, Wendy T; Woods-Townsend, Kathryn; Vogel, Christina A; Farrell, David; Inskip, Hazel; Baird, Janis; Morrison, Leanne; Barker, Mary; Strömmer, Sofia T
Abstract: Objective: To identify the ways in which parental involvement can be incorporated into interventions to support adolescent health behaviour change. Design: Data from semi-structured interviews were analysed using inductive thematic analysis. Setting: Southampton, Hampshire, UK. Participants: A convenience sample of twenty-four parents of adolescents. Results: Parents consider themselves to play an important role in supporting their adolescents to make healthy choices. Parents saw themselves as gatekeepers of the household and as role models to their adolescents but recognised this could be both positive and negative in terms of health behaviours. Parents described the changing dynamics of the relationships they have with their adolescents because of increased adolescent autonomy. Parents stated that these changes altered their level of influence over adolescents' health behaviours. Parents considered it important to promote independence in their adolescents; however, many described this as challenging because they believed their adolescents were likely to make unhealthy decisions if not given guidance. Parents reported difficulty in supporting adolescents in a way that was not viewed as forceful or pressuring. Conclusions: When designing adolescent health interventions that include parental components, researchers need to be aware of the disconnect between public health recommendations and the everyday reality for adolescents and their parents. Parental involvement in adolescent interventions could be helpful but needs to be done in a manner that is acceptable to both adolescents and parents. The findings of this study may be useful to inform interventions which need to consider the transitions and negotiations which are common in homes containing adolescents.